1992
DOI: 10.1182/blood.v79.11.2827.2827
|View full text |Cite
|
Sign up to set email alerts
|

Double-intensive therapy in high-risk multiple myeloma

Abstract: A high remission rate is achieved with high-dose melphalan (HDM) in multiple myeloma (MM), and autologous transplantation of hematopoietic stem cells allows a prompt hematologic recovery after high-dose therapy. We treated 97 patients with high-risk MM (group 1:44 advanced MM including 14 primary resistances and 30 relapses; group 2: 53 newly diagnosed MM) with a first course of HDM. For responding patients a second course of high-dose therapy with hematopoietic stem cell support was proposed. After the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 25 publications
0
26
0
2
Order By: Relevance
“…Patients in apparent CR had a median survival of 67 months versus 33 months for patients who did not achieve CR (and 47 months for patients achieving only PR). In a previous study on double-intensive therapy, we have already shown that the response to the first course of HDM has a great impact on survival [6]. In a pilot study of ABMT for previously untreated patients, one of us also reported that the duration of response was affected by the magnitude of response [4].…”
Section: Discussionmentioning
confidence: 93%
“…Patients in apparent CR had a median survival of 67 months versus 33 months for patients who did not achieve CR (and 47 months for patients achieving only PR). In a previous study on double-intensive therapy, we have already shown that the response to the first course of HDM has a great impact on survival [6]. In a pilot study of ABMT for previously untreated patients, one of us also reported that the duration of response was affected by the magnitude of response [4].…”
Section: Discussionmentioning
confidence: 93%
“…The median survival of our patients younger than 40 years who had normal renal function or low serum 2 -microglobulin levels was about 8 years. This long survival in young patients with MM treated with conventional chemotherapy should be considered when evaluating the results in patients receiving more intensive therapy such as bone marrow transplantation (Gahrton et al, 1991;Attal et al, 1992;Harousseau et al, 1992;Jagannath et al, 1992). Patients who also have a low plasma cell labelling index might have an even longer median survival.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chemotherapy in MM is palliative and does not usually result in long-lasting responses, even when intensive regimens such as VAD or high-dose melphalan are used (Gore et al, 1989;Samson et al, 1989;Lokhorst et al, 1992). For this reason, the efficacy of high-dose therapy followed by autologous or allogeneic stem cell support is currently being investigated (Gahrton et al, 1991;Attal et al, 1992;Harousseau et al, 1992;Jagannath et al, 1992;Alexanian & Dimopoulos, 1994). Although a median survival of 54 months is the longest reported so far in long-term studies of MM, it is still unsatisfactory, especially in persons younger than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged severe neutropenia is one of the major adverse effects and dose-limiting toxicities of HDM, which in some patients leads to serious infections and other complications. 6,7 Granulocyte-colony stimulating factor (G-CSF) is given to restore circulating neutrophils after chemotherapyinduced neutropenia in MM, although the timing for starting G-CSF after transplant varies among institutions. 8 Recent studies conducted by our group and prior studies by others have also demonstrated that the G-CSF regimen can significantly influence the duration of neutropenia following ASCT.…”
Section: Wwwpsp-journalcommentioning
confidence: 99%